2023
DOI: 10.1021/acsapm.3c00636
|View full text |Cite
|
Sign up to set email alerts
|

Highly Ion-Conductive and Alkaline Stable Anion Exchange Membranes Containing Bulky Aryl Units and Symmetric bis-Piperidinium Branches

Abstract: The challenge in developing high-performance anion exchange membranes (AEMs) involves achieving high ion conductivity while maintaining sufficient alkaline and mechanical stability. In this work, an aromatic monomer [bis(4′-(1,5-dibromopentan-3-yl)phenyl)-1,4-terphenyl (BBTP)] with a bulky aryl unit and symmetric dibrominated branches was first designed and synthesized. Then, BBTP was used to prepare aryl ether-free AEMs (QPTPDP-x-OH) via the superacid-catalyzed polyhydroxyalkylation and Menshutkin reactions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 65 publications
(130 reference statements)
0
2
0
Order By: Relevance
“…Therefore, obtaining higher ionic conductivity with a smaller IEC is becoming more attractive in the AEM research fields. The function of the IEC and the ionic conductivity of the AEM Q-BOC-OEC-1/1 are compared with the literatures, as shown in Figure b. ,,,,,,,,,,, The AEM prepared in this study demonstrated higher ionic conductivity and compared other AEMs with similar IEC due to the effect of their synergistic dual functional side chains, in addition, some poly­(arylene-alkylene)-based AEMs demonstrated high performance similar to Q-BOC-OEC-1/1 attributed to the distinct phase separation between the hydrophobic main chain and the hydrophilic side chain. As one kind of poly­(arylene-alkylene)-based AEMs, the membrane Q-BOC-OEC-1/1 in this work chooses carbazole as the aryl group, which still has the same advantages in terms of morphology construction-induced ion transport.…”
Section: Resultsmentioning
confidence: 73%
“…Therefore, obtaining higher ionic conductivity with a smaller IEC is becoming more attractive in the AEM research fields. The function of the IEC and the ionic conductivity of the AEM Q-BOC-OEC-1/1 are compared with the literatures, as shown in Figure b. ,,,,,,,,,,, The AEM prepared in this study demonstrated higher ionic conductivity and compared other AEMs with similar IEC due to the effect of their synergistic dual functional side chains, in addition, some poly­(arylene-alkylene)-based AEMs demonstrated high performance similar to Q-BOC-OEC-1/1 attributed to the distinct phase separation between the hydrophobic main chain and the hydrophilic side chain. As one kind of poly­(arylene-alkylene)-based AEMs, the membrane Q-BOC-OEC-1/1 in this work chooses carbazole as the aryl group, which still has the same advantages in terms of morphology construction-induced ion transport.…”
Section: Resultsmentioning
confidence: 73%
“…20,36,37 Polyarylene-based AEMs, characterized by a rigid structure, exhibit a WU ≤ 100% and an SR ≤ 20%. 43–49 Regarding the x -PDB- m -F5-SEBS membranes, the WU ranges from 90.7–111.1%, with an SR of 25.0–30.2%, values falling between the SEBS- and polyarylene-based AEMs. Hence, excessive membrane expansion typically associated with SEBS is effectively suppressed and enhanced dimensional stability is achieved.…”
Section: Resultsmentioning
confidence: 99%